Formative evaluation of an Arabic online vocabulary learning games prototype: lessons from a Malaysian higher learning institution experience - Sahrir, Muhammad Sabri (IGI Global, United States, 2012)
The use of digital game-based learning is a new trend of instructional practices in different fields of knowledge. The research and studies related to this field are increasingly attracting the researchers all over the world to further explore the various aspects of educational games models, the design and development of games itself, the evaluation insights and many more. This chapter describes an experience of the formative evaluation of an online game among Arabic language learners at the elementary level in the International Islamic University Malaysia (IIUM). The mixed methods of quantitative and qualitative research approaches were utilized to investigate the usability, practicality and effectiveness of this games prototype in the real settings. This chapter also described the process and phases of evaluation throughout the responses from participants which vary from experts in ID and SME, lecturers and learners as the actual users.